2021
DOI: 10.1136/emermed-2020-210212
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital risk stratification in patients with chest pain

Abstract: ObjectivesThe History, ECG, Age, Risk Factors and Troponin (HEART) Score is a decision support tool applied by physicians in the emergency department developed to risk stratify low-risk patients presenting with chest pain. We assessed the potential value of this tool in prehospital setting, when applied by emergency medical services (EMS), and derived and validated a tool adapted to the prehospital setting in order to determine if it could assist with decisions regarding conveyance to a hospital.MethodsIn 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Several studies have shown that paramedic risk assessment and point-of-care troponin testing are feasible in the prehospital setting, with minimal delays in transport times to the hospital. [5][6][7][8][9][10] In some studies, prehospital blood draws for immediate testing on arrival to the ED have been associated with reduced ED length of stay, results that might be extrapolated to prehospital point-of-care troponin testing. 6,8 In the Netherlands, 1 trial using prehospital risk assessment and serial point-of-care troponin testing (via 2 ambulance visits) categorized 28% of the cohort as low risk, with these patients referred to other health services rather than being transported to the ED with similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that paramedic risk assessment and point-of-care troponin testing are feasible in the prehospital setting, with minimal delays in transport times to the hospital. [5][6][7][8][9][10] In some studies, prehospital blood draws for immediate testing on arrival to the ED have been associated with reduced ED length of stay, results that might be extrapolated to prehospital point-of-care troponin testing. 6,8 In the Netherlands, 1 trial using prehospital risk assessment and serial point-of-care troponin testing (via 2 ambulance visits) categorized 28% of the cohort as low risk, with these patients referred to other health services rather than being transported to the ED with similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NHS24 telephone triage and PCOOH do not have access to diagnostic tools such as troponin and ECG. Pre-hospital use of these investigations by emergency medical services has been shown to aid conveyance decisions,28 but further research is needed as to whether access to point-of-care troponin in ambulance services and PCOOH would improve outcomes and reduce referrals. Research is also needed to examine the characteristics and outcomes of patients that each service discharges as well as those that are referred to other UC services for further assessment, particularly if telephone triage is to become the single point of entry for those attempting to access UC.…”
Section: Discussionmentioning
confidence: 99%
“…In an intervention centre, time from admission to revascularisation was shorter than in a general hospital [8 days (5)(6)(7)(8)(9)(10)(11)(12) vs. 10 days (7-14), p = < 0.001]. Total length of stay was shorter in an intervention centre compared to a general hospital [16 days (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) vs. 18 days (14-23), p < 0.001]. In MACE, no difference was found between the hospitals [9.2% vs. 10.8%, p = 0.481].…”
Section: Cabg Cohortmentioning
confidence: 99%
“…An example of such scores are the preHEART and the modi ed HEART pathway which use the patients' history, ECG, risk factors and a Point-of-Care (POC) Troponin. (15,16) These scores provide paramedics with the opportunity to make a strati cation of likelihood for patients with undifferentiated chest pain for having a NSTEMI. The likelihood ratio of combined risk scores for risk strati cation in suspected NSTEMI patients are currently better then standalone history, ECG and, POC-Troponin alone.…”
Section: Pre-hospital Triagementioning
confidence: 99%